Atom removal on the basal plane of layered MoS2 leading to extraordinarily enhanced electrocatalytic performance. (10th March 2020) - Wang, Chao; Lu, Haoliang; Tang, Kai; Mao, Zeyang; Li, Qun; Wang, Xianfu; Yan, Chenglin
Abstract: Efficient utilization of sulfur atom in MoS2 -based electrocatalysts on the basal plane is highly desirable and expectable to optimize the electrocatalytic performance for hydrogen evolution reaction (HER). Herein, removing atoms on the basal plane of layered MoS2 by Li-ion intercalation leading to extraordinarily enhanced electrocatalytic performance is newly reported, which provides a novel way to active the basal planes of layered transition metal sulfides towards hydrogen evolution. It is found that the desulfurization of layered MoS2 can bring atomic vacancies on the basal plane, which is confirmed to be active sites towards hydrogen evolution experimentally and theoretically. The first-principle calculations reveal that the desulfurization induced atomic vacancies not only reduce the free energy of hydrogen adsorption (ΔGH* ), but also accelerate the electron transfer on the basal plane. Besides, the phase transformation from 2H to 1T during the electrochemical lithium-ion intercalation could reach higher electronic conductivity, thus further optimize the HER kinetics through phase engineering. For these reasons, the desulfurized MoS2 displays improved HER activity with lowered overpotential of 200 mV to obtain 10 mA cm −2, high stability, decreased Tafel slope of 65 mV dec −1 and enhanced TOF of 0.093H2 s −1 at overpotential of 250 mV, which are much better than that of the pristine MoS2 and other optimized MoS2 -based catalysts.